PENGEMBANGAN MEDIA PEMBELAJARAN BANDICAM BERBASIS POWER POINT DALAM PEMBELAJARAN PRAKARYA DAN KEWIRAUSAHAAN KELAS X SMA PEMBANGUNAN - Novitri Angraini; Suib Awrus (Serupa The Journal of Art Education, 2021)
Developing a Power point based Bandicam learning media in craft and entrepreneurship learning for class X in SMA Pembangunan this is valid and practical is the purpose of this research. This study uses a research and development method using 4D model. The subject of the product trial involved four validators, including two material validators, one language validator, and one mediator. The subjects of this study also involved grade X students with a total of 10 people as a practicality test. For data collection using a questionnaires. The results of this study state that the product that the author developed is declared very valid and very practical to use in craft and entrepreneurship learning. With the average validation is 92.60% with very valid category and the average practicality of students is 87.15% very practical category.Keyword: Learning Media, Bandicam, Craftsmanship and Entrepreneurship.